Privacy, property and personality: Civil law perspectives on commercial appropriation - Smith, Huw Beverley (Cambridge University, 2013)
The protection of privacy and personality is one of the most fascinating issues confronting any legal system. This book provides a detailed comparative analysis of intellectual property rights in an individual's name, voice or likeness in the major legal systems: France, Germany, the United Kingdom and the United States.